Behavioural output of ahand goal-directed aiming task during rapid learning and neuromuscular fatigue / Elaheh Amini - Elaheh , Amini (2021)
Goal-directed aiming task requires a highly accurate movement of the limb from the onset to the desired target. This aiming movement consists of two components, (i) the initial adjustment of a rapid phase that regulates limb direction and velocity to the vicinity of the target, and (ii) late error correction phase, where visual and other forms of feedback are utilized to reduce aiming errors. The integration of sensory information from visual, proprioceptive, tactile, spatial etc. to the brain for precision of movement planning transforms into speed, accuracy, and energy optimization. When confronting changes to these sensory inputs and external related factors occur (i.e., neuromuscular fatigue), subsequent alteration to movement planning occurs, which in turn affects behavioural output. Thus, these adaptations could affect internal model of governing goal-directed aiming. The aim of this thesis was to investigate the processes of sensorimotor adaptation of a hand goal-directed aiming task, confronting (i) changes in spatial (i.e., hand orientation) with and without directional visual feedback during and following rapid-learning phase, and (ii) challenges to neuromuscular fatigue during low and high force production. It has been established that directional errors in a goal-directed aiming task are not consistent towards different targets in a workspace, which are commonly regarded as inherent bias. However, when there is a hand rotation, it is unknown whether the inherent bias shifts according to joint, muscle, and/or visual space in different component of goal-directed aiming task. In Chapter 3, the shift in inherent bias was analysed from neutral to pronated hand position at every 22.5 o and vice-versa. It was discovered that the shift in inherent bias is dominantly according to joint space rather than muscle or extrinsic reference frame. Short-term adaptation is also known to have a distinct mechanism upstream to primary motor cortex (M1) which is evident through visuomotor and force-field tasks. In Chapter 4, this adaptation in a goal-directed aiming task was tested by manipulating hand orientations (neutral and pronated) during rapid learning phase (familiarisation) with visual feedback. Then, the directional errors and learning rate were compared between different hand orientations. It was discovered that it is highly probable for a goal-directed aiming task to have similar mechanisms to short-term adaptation, generally observed in motor adaptations. When visual feedback was removed, there was no additional learning for both hand orientations and errors remain consistent with subsequent trials, alternating between with and without visual feedback. Hence, it was concluded that higher centres are likely governing the internal model that controls the aiming task without visual feedback. Low- and high-force fatiguing task are believed to be governed by different mechanisms (varying central and peripheral contributions). In Chapter 5, a goal-directed aiming was assessed following fatiguing tasks to determine the movement accuracy. The findings indicate that low-force fatiguing contraction (15% MVC) until task failure induces greater errors in goal-directed aiming task compared to high-force ones, even when the high neural drive before task failure were eliminated by inducing low-force fatiguing contraction for 70% of the time to task failure until task failure occurs. Hence, a goal-directed aiming requires greater central contribution and affects the control systems that are involved in task execution. In summary, mechanisms involved in goal-directed aiming short-term adaptation are likely similar to other motor tasks i.e., visuomotor rotation. Central fatigue is also found to negatively affect the goal-directed aiming task performance. In addition, the inherent bias seen in a goal-directed aiming task shifts according to joint-space with hand rotation. The findings collectively provide insights to the factors contributing to the goal-directed aiming task models and in addition to better design of a motor control aiming task for rehabilitation purposes.